(untitled) (Journal of Bio-Science, 2018)
Ramshagar dighi is a larger historical man made reservoir (Dighi, Bengali meaning) situated at Tajpur village in Dinajpur, Bangladesh. This study was aimed to estimate current status of physico-chemical variables of water of Ramshagar dighi at Dinajpur District, Bangladesh. Monthly average changes in physico-chemical parameters such as water temperature, total dissolved oxygen, air temperature, humidity, rainfall, water depth and pH of water were analyzed for the period of 11 months from May 2011 to March 2012. The average air temperature (°C) at the study area of Ramshagar dighi at Dinajpur District was determined as 24.97 ± 4.92. Our present study showed that physico-chemical properties of water in Ramshagar dighi were monthly average of water temperature (°C) as 24.68 ± 4.77, air temperature (°C) 24.97 ± 4.92, humidity as 82.075 ± 4.14, rainfall as 1534.5 mm, water depth as 9.10 m ± 1.286, pH as7.67± 0.48 and carbon dioxide as 0.85 ± 0.92 as well as dissolved oxygen as 4.65 ± 0.62 respectively during the period of May 2011 to March 2012. Therefore, present study was conducted to assess physico-chemical properties of water of Ramshagar dighi, Dinajpur, Bangladesh. J. bio-sci. 23: 29-37, 2015